Studi Komparasi Strategi Examples Non Examples Dan Picture And Picture Terhadap Hasil Belajar IPSKelas IV SD Muhammadiyah 3 Surakarta Tahun 2015/2016 - Aji, Toni Perguri Raditya; , Drs. Muhroji, S.E.,M.Pd (2016)
Abstracts This study aims to determine: (1) The difference in the results of social studies through the use of strategies Examples of non examples and Picture and picture in the fourth grade students of SD Muhammadiyah Surakarta 3 2015 / 2016. (2) A better strategy for learning outcomes IPS obtained between examples using a strategy of non examples and strategies Picture and picture. This study included a quantitative study with an experimental model, the research subjects graders IVA and IVB 3 SD Muhammadiyah Surakarta. The data collection technique using the techniques of tests and documentation. Test instrument is used to test the validity and reliability testing. Data were analyzed using t-test technique which preceded the prerequisite test analysis, the test of normality and homogeneity test. Based on data analysis with a significance level of 5% was obtained t_hitung> t_tabel, namely 2.060> 1.997. And obtained a mean value between grade classes are taught using the strategy Examples of non examples and classes are taught using the strategy Picture and picture 79.85> 74.17. The conclusion of this study were (1) there is a difference between the effects of non examples and strategies Examples Picture and picture on learning outcomes IPS fourth grade students of SD Muhammadiyah Surakarta 3 Year 2015/2016. (2) Examples of non examples strategies are better than Picture and picture of the results of the fourth grade social studies Surakarta Muhammadiyah 3 Year 2015/2016. Keywords: Social Science Learning Outcomes, Examples of non examples Picture and picture.